Regenerative potential of leucocyte‐ and platelet‐rich fibrin. Part A: intra‐bony defects, furcation defects and periodontal plastic surgery. A systematic review and meta‐analysis. (24th November 2016) - Castro, Ana B.; Meschi, Nastaran; Temmerman, Andy; Pinto, Nelson; Lambrechts, Paul; Teughels, Wim; Quirynen, Marc
Abstract: Aim: To analyse the regenerative potential of leucocyte‐ and platelet‐rich fibrin (L‐PRF) during periodontal surgery. Materials and Methods: An electronic and hand search were conducted in three databases. Only randomized clinical trials were selected and no follow‐up limitation was applied. Pocket depth (PD), clinical attachment level (CAL), bone fill, keratinized tissue width (KTW), recession reduction and root coverage (%) were considered as outcome. When possible, meta‐analysis was performed. Results: Twenty‐four articles fulfilled the inclusion and exclusion criteria. Three subgroups were created: intra‐bony defects (IBDs), furcation defects and periodontal plastic surgery. Meta‐analysis was performed in all the subgroups. Significant PD reduction (1.1 ± 0.5 mm, p  < 0.001), CAL gain (1.2 ± 0.6 mm, p  < 0.001) and bone fill (1.7 ± 0.7 mm, p  < 0.001) were found when comparing L‐PRF to open flap debridement (OFD) in IBDs. For furcation defects, significant PD reduction (1.9 ± 1.5 mm, p  = 0.01), CAL gain (1.3 ± 0.4 mm, p  < 0.001) and bone fill (1.5 ± 0.3 mm, p  < 0.001) were reported when comparing L‐PRF to OFD. When L‐PRF was compared to a connective tissue graft, similar outcomes were recorded for PD reduction (0.2 ± 0.3 mm, p  > 0.05), CAL gain (0.2 ± 0.5 mm, p  > 0.05), KTW (0.3 ± 0.4 mm, p  > 0.05) and recession reduction (0.2 ± 0.3 mm, p  > 0.05). Conclusions: L‐PRF enhances periodontal wound healing.